Biomass and nutritional quality of four varieties of alfalfa to be introduced in Pamplona, Colombia (2018)
This study was carried out at the Center of Research in Plant Health and Bioinsumes of the University of Pamplona (Norte de Santander), with the objective of evaluating the productivity and nutritional quality of four alfalfa (Medicago sativa L.) varieties: Cuf 101, Moapa 69, SW-8210, and SW-8718. An experiment was carried out with four randomized treatments with three replicates, for a total of 12 experimental units of 9 m2 each. The application of correctives and amendments was done one-week prior planting, based on soil analysis. At day 70 of the sowing, a pairing cut was made to homogenize each plot. Measurements of green biomass production and nutritional quality were determined at the floral bud stage, at 210 days after sowing. The ANOVA tests showed no significant differences among the alfalfa varieties for the environmental conditions of the municipality of Pamplona, which means that all varieties can be introduced in this agroecosystem.